Targeting Adenosine Receptors for the Treatment of Cardiac Fibrosis - Vecchio, Elizabeth A.; White, Paul J.; May, Lauren T. (Frontiers in Pharmacology, 2017)
Adenosine is a ubiquitous molecule with key regulatory and cytoprotective mechanisms at times of metabolic imbalance in the body. Among a plethora of physiological actions, adenosine has an important role in attenuating ischaemia-reperfusion injury and modulating the ensuing fibrosis and tissue remodelling following myocardial damage. Adenosine exerts these actions through interaction with four adenosine G protein-coupled receptors expressed in the heart. The adenosine A2B receptor (A2BAR) is the most abundant adenosine receptor in cardiac fibroblasts and is largely responsible for the influence of adenosine on cardiac fibrosis. In vitro and in vivo studies demonstrate that acute A2BAR stimulation can decrease fibrosis through the inhibition of fibroblast proliferation and reduction in collagen synthesis. However, in contrast, there is also evidence that chronic A2BAR antagonism reduces tissue fibrosis. This review explores the opposing pro- and anti-fibrotic activity attributed to the activation of cardiac adenosine receptors and investigates the therapeutic potential of targeting adenosine receptors for the treatment of cardiac fibrosis.